2013
DOI: 10.1098/rspb.2013.0035
|View full text |Cite
|
Sign up to set email alerts
|

Socially synchronized circadian oscillators

Abstract: Daily rhythms of physiology and behaviour are governed by an endogenous timekeeping mechanism (a circadian 'clock'). The alternation of environmental light and darkness synchronizes (entrains) these rhythms to the natural day-night cycle, and underlying mechanisms have been investigated using singly housed animals in the laboratory. But, most species ordinarily would not live out their lives in such seclusion; in their natural habitats, they interact with other individuals, and some live in colonies with highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 107 publications
4
66
0
Order By: Relevance
“…Just like daily rhythms [70], annual rhythms regulate functions whose value often depends on interactions with conspecifics, ranging from temporal mating associations to colony or flock formation for reproduction and movement [55]. Many organisms thus synchronize their activities to those of conspecifics.…”
Section: (D) Temperature and Other Factorsmentioning
confidence: 99%
“…Just like daily rhythms [70], annual rhythms regulate functions whose value often depends on interactions with conspecifics, ranging from temporal mating associations to colony or flock formation for reproduction and movement [55]. Many organisms thus synchronize their activities to those of conspecifics.…”
Section: (D) Temperature and Other Factorsmentioning
confidence: 99%
“…Studies with other social insects might provide some clues. For example, it has been suggested that foraging honeybees may somehow synchronize their biological rhythms and inform nestmates about external environmental conditions through their body movements (Bloch et al, 2013). Another possibility could be some sort of chemical signaling that would induce entire nest populations to enter or terminate diapause.…”
Section: Autumn / Winter Spring / Summermentioning
confidence: 99%
“…Synchronization of coupled self-sustained oscillating systems is a ubiquitous phenomenon in nature and appears in fields as diverse as biology [1][2][3], economics [4], sociology [5] and physics, where it was first scientifically described [6]. In the latter field an interesting question is what happens with synchronization in the quantum regime, i.e.…”
Section: Introductionmentioning
confidence: 99%